Efficiency limiting factors of petrochemical wastewater treatment using hybrid biological reactor - Ahmed, Mohd Elmuntasir; Mydlarczyk, Andrzej; Al-Haddad, Adel (Journal of Environmental Engineering and Landscape Management, 2022)
The wastewater characteristics and some operational control parameters limit the efficiency of attached growth processes for petrochemical wastewater treatment. This study aims to determine the efficiency of a hybrid biological reactor treating actual petrochemical wastewater and to identify the efficiency determining factors. An up-flow biological reactor filled with bio-career was operated at two flow rates, two dissolved oxygen (DO) levels, and under anaerobic conditions. Due to the varying characteristics of actual petrochemical wastewater, efficiency limitations were manifested in many ways. However, the highest chemical oxygen demand and biochemical oxygen demand (BOD) removal efficiencies were 77.2% and 78.5%, respectively, and were achieved under aerobic operation at organic loading rates (OLRs) of 0.2 kg-COD/m3/d and hydraulic retention time (HRT) of 26.67 h (DO 4.0 mg/l). Anaerobically, the highest efficiency was 41.7 for both at 0.18 kg-COD/m3/d and 400 ml/min. The total organic carbon (TOC) removal stability was attributed to the presence of toxic chemicals and removal mechanisms other than biodegradation, as it tapered off at high loading. The nutrient removal efficiency was marginal, conceivably due to the high organics to nutrient ratio and toxic conditions of the wastewater promoting nutrient removal inside the biofilm.